2015
DOI: 10.1007/978-3-319-23826-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Prefix and Suffix Reversals on Strings

Abstract: International audienceThe Sorting by Prefix Reversals problem consists insorting the elements of a given permutation π with a minimum numberof prefix reversals, i.e. reversals that always imply the leftmost elementof π. A natural extension of this problem is to consider strings (inwhich any letter may appear several times) rather than permutations. Instrings, three different types of problems arise: grouping (starting from astring S, transform it so that all identical letters are consecutive), sorting(a constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The number in parenthesis in this table is the maximum difference between the prefix and suffix distance and the prefix distance. We note that Fertin et al [29] showed that, for infinitely many values of n, there is a permutation of size n such that the difference between the prefix reversal distance and the prefix and suffix reversal distance is Ω(n).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The number in parenthesis in this table is the maximum difference between the prefix and suffix distance and the prefix distance. We note that Fertin et al [29] showed that, for infinitely many values of n, there is a permutation of size n such that the difference between the prefix reversal distance and the prefix and suffix reversal distance is Ω(n).…”
Section: Introductionmentioning
confidence: 86%
“…In this section we present an algorithm for SbPSR problem, which was recently proved to be NP-hard by Fertin et al [29]. The general idea of our algorithm is, while the permutation is not sorted: try to apply a 1-move or else a 1-move followed by a 0-move; if neither is possible, the permutation has a specific format that can be sorted with at most its number of breakpoint operations.…”
Section: Sorting By Prefix and Suffix Reversalsmentioning
confidence: 99%
“…Considerando os eventos de reversão e transposição de prefixo ou sufixo, quase todas as variações possuem complexidade desconhecida, com exceção do problema de Ordenação de Permutações por Reversões de Prefixo ou Sufixo, que pertence à classe de problemas NP-Difíceis [18].…”
Section: Introductionunclassified